Self-differentiation and eating disorders in early and middle adolescence: A cross-sectional path analysis. (April 2018) - Doba, Karyn; Berna, Guillaume; Constant, Emilie; Nandrino, Jean-Louis
Abstract: This study examines the impact of self-differentiation, alexithymia and psychological distress on eating disorder symptoms in young and middle adolescence. Four hundred fifty-one adolescents completed self-report measures. Early and middle adolescents were categorized into two groups (12–14 years and 15–17 years) to represent distinct developmental stages. Significant differences were found between younger and older adolescents. The association between low self-differentiation and both eating disorders symptoms and psychological dimensions related to eating attitudes was stronger in early adolescence than in middle adolescence. The association between low self-differentiation and eating disorder symptoms was mediated by alexithymia and psychological distress in middle adolescence. Taken together, these findings suggest that self-differentiation could be useful in understanding psychological distress and alexithymia in eating disorders. Highlights: Low levels of self-differentiation are associated with eating disorder symptoms in early and middle adolescence. The association between low levels of self-differentiation and eating disorder symptoms is stronger in early adolescence, compared with middle adolescence. The association between low levels of self-differentiation and eating disorder symptoms is mediated by alexithymia and psychological distress in middle adolescence.